More than a common acid buffering in the treatment of Non-Erosive GERD-like Clinical Spectrum: A Chios Masthia-based Formulation with (Cyto) Protecting Effect - Barreto R; Todai M; Kumar N; Hayakawa K; Marotta F; Imaoka Y; Catanzaro R (Archives of Clinical Gastroenterology - Peertechz Publications, 2019)
The aim of this study was to test the clinical and mucosal benefit of a natural gastro-oesophageal mucosal protector DOGDG-121 in non-erosive GERD comprising from NERD, to Functional Heartburn and Hypersensitive oesophagus while also ascertain the symptom-free duration in patients with prior symptomatic relapsing GERD. 68 consecutive adult patients, reporting mild heartburn symptoms two or more days a week or at least moderate symptoms more than once a week for at least six months duration were prospectively recruited. Inclusion criteria were: recurrent typical GERD symptoms, such as heartburn and/or acid regurgitation and a duration of symptoms>6 months. Patients were divided in two groups comparable as for age, gender, BMI and pHmetry profile. One group was given 1 sachet a day (2gr) of DOGDG-121 (chios masthia- and musa extract-based phytocompound, Reflumed, Named, Italy) quickly stirred in a small water quantity (≤30ml) and swallowed at once, while the other was administered 5ml of a buffering antacid suspension (BAS) (Dried Aluminium Hydroxide Gel 230mg,Magnesium Hydroxide 200mg Simeticone 25mg)as positive control. At entry and after 12 weeks all patients underwent an ambulatory 24-Hours intraesophageal pH monitoring. As compared to BAS, DOGDG-121 enabled a significantly lesser degree of microscopic oesophagitis, reduced gene expression of IL-8 and all Eotaxins tested (p<0.05). This was also associated to a better gastrointestinal-related quality of life assessment (p<0.05). This strongly suggested that, besides protection against acido-peptic mucosal injury per sè, DOGDG-121 appears to offer a more significant effect on inflammatory mediators interfering with peripheral nociceptors, being amenable to safe, long-term cytoprotective use.